2014
DOI: 10.1371/journal.pone.0107806
|View full text |Cite
|
Sign up to set email alerts
|

Aphid Honeydew Quality as a Food Source for Parasitoids Is Maintained in Bt Cotton

Abstract: Bt-transgenic cotton has proven to be highly efficient in controlling key lepidopteran pests. One concern with the deployment of Bt cotton varieties is the potential proliferation of non-target pests. We previously showed that Bt cotton contained lower concentrations of insecticidal terpenoids as a result of reduced caterpillar damage, which benefited the aphid Aphis gossypii. It is thus important that non-target herbivores are under biological control in Bt cotton fields. The induction or lack of induction of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 49 publications
1
13
0
1
Order By: Relevance
“…Similarly to the results non-Bt maize plants results, the pre-infestation of Bt maize plants by T. urticae did not resulted in significant reductions of the mite survival and reproductive abilities. Although not directly addressed here, other investigations (HAGENBUCHER et al, 2014) have shown that Bt and non-Bt cotton plants did not differ in terpenoid levels when they were previously subjected to jasmonate treatments.…”
Section: Contentsmentioning
confidence: 81%
“…Similarly to the results non-Bt maize plants results, the pre-infestation of Bt maize plants by T. urticae did not resulted in significant reductions of the mite survival and reproductive abilities. Although not directly addressed here, other investigations (HAGENBUCHER et al, 2014) have shown that Bt and non-Bt cotton plants did not differ in terpenoid levels when they were previously subjected to jasmonate treatments.…”
Section: Contentsmentioning
confidence: 81%
“…It was reported that honeydew volatiles are important kairomones for parasitoids and predators, and these volatiles can improve the efficacy of natural enemies (Almohamad et al, 2009;Leroy et al, 2011). Many studies have indicated that the composition of aphid honeydew obviously influences the performance of aphid enemies (Hogervorst et al, 2007;Hagenbucher et al, 2014;Tena et al, 2016;Zhou et al, 2016;Benelli et al, 2017). However, relatively few studies have evaluated the quantitative effects.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to feeding on host hemolymph, parasitoid females require sugar food sources such as floral nectar and/or honeydew in order to sustain biological traits linked to actual parasitoid fitness (Jervis et al 2001;Wäckers et al 2008;Benelli et al 2017). Honeydew consumption has been shown to increase parasitoid longevity (Hogervorst et al 2007;Hagenbucher et al 2014;Tena et al 2018) and may be involved in parasitoid performance, e.g., by increasing offspring production (Lahiri et al 2017;Dong et al 2018;Picciau et al 2019); this has notably been reported for N. artynes feeding on floral nectar (Balzan and Wäckers 2013) as well as for N. tutae feeding on whitefly honeydew (Dong et al 2018). We demonstrate further that tomato aphid honeydew enhances N. tutae adult longevity under laboratory conditions (Fig.…”
Section: Impact Of Honeydewmentioning
confidence: 99%